2022
DOI: 10.34306/att.v4i2.122
|View full text |Cite
|
Sign up to set email alerts
|

Digital Ilearning Chain Scheme in Education Blockchain Based

Abstract: In the era of the digital revolution, the use of technology has made technology a major demand, coupled with the development of insight and techniques, technology in this era has been widely used in all scientific fields. In the field of monetary economics, there are payment instruments that can be used to transact both in the form of goods and services. However, nowadays it is difficult to obtain information as technology develops, the term digital transaction appears. Because many activities are carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
2
0
3
Order By: Relevance
“…2. This study also finds that the disclosure of corporate social responsibility in companies does not affect the financial performance of manufacturing companies in Indonesia [16] [17].This study also found that the disclosure of carbon emissions and CSR simultaneously affect the financial performance of Manufacturing Companies in Indonesia [18] [19] [20] with the results of Cross-Section Fixed data processing results of 78%. The two variables used, namely CED and CSR can explain financial performance and the rest is influenced by other variables that are not tested in this study [21] [22] [23].…”
Section: Simultaneous Effect Test Results (F-test)mentioning
confidence: 68%
“…2. This study also finds that the disclosure of corporate social responsibility in companies does not affect the financial performance of manufacturing companies in Indonesia [16] [17].This study also found that the disclosure of carbon emissions and CSR simultaneously affect the financial performance of Manufacturing Companies in Indonesia [18] [19] [20] with the results of Cross-Section Fixed data processing results of 78%. The two variables used, namely CED and CSR can explain financial performance and the rest is influenced by other variables that are not tested in this study [21] [22] [23].…”
Section: Simultaneous Effect Test Results (F-test)mentioning
confidence: 68%
“…The capability of AI to conduct in-depth data analysis and predict business trends empowers companies to identify novel opportunities and make more informed strategic decisions [36]. Consequently, artificial intelligence not only streamlines internal processes but also cultivates a business environment that is adaptable to changean essential element for sustainable entrepreneurship [37]. Furthermore, AI's support for innovation can establish a competitive edge for companies within a constantly evolving market.…”
Section: Artificial Intelligence and Entrepreneurial Performancementioning
confidence: 99%
“…Gaya purposive sampling cukup bermanfaat dalam analisis data yang dikumpulkan dari sejumlah kecil sampel dalam studi penelitian.memiliki keunggulan membantu dalam menentukan analisis data. [22]. Memberikan Proses Penerbitan Sertifikat Digital, dan memberikan proses verifikasi menggunakan Blockchain.…”
Section: Metodologi Penelitianunclassified